Diurnal Variation of Soil Heat Flux at an Antarctic Local Area during Warmer Months - Marco Alves; Jacyra Soares (Applied and Environmental Soil Science)
Soil heat flux (G) is one term in the energy balance equation, and it can be particularly important in regions with arid, bare, or thinly vegetated soil surfaces. However, in remote areas such as the Antarctic, this measurement is not routinely performed. The analysis of observational data collected by the ETA Project at the Brazilian Antarctic Station from December 2013 to March 2014 showed that, for the total daily energy flux, the surface soil flux heats the deeper soil layers during December and January and G acts as a heat source to the outer soil layers during February and March. With regard to daytime energy flux, G acts as a source of heat to the deeper layers. During the night-time, the soil is a heat source to the shallower soil layers and represents at least 29% of the net night-time radiation. A relatively simple method—the objective hysteresis method (OHM)—was successfully applied to determine the surface soil heat flux using net radiation observations. A priori, the OHM coefficients obtained in this study may only be used for short-time parameterizations and for filling data gaps at this specific site.